Quantification of Hydrogen Peroxide in Cretan Honey and Correlation with Physicochemical Parameters - Amalia Alygizou; Spyros Grigorakis; Panagiota Gotsiou; Sofia Loupassaki; Antony C. Calokerinos (Journal of Analytical Methods in Chemistry)
The aim of the present study is to quantify hydrogen peroxide, generated from various types of honey produced in Crete, as a potent antimicrobial agent, and establish any correlation with their physicochemical parameters. The basic physicochemical parameters (diastase activity, HMF content, moisture, electrical conductivity, color, and sugars) of 30 authentic honey samples were determined. The concentration of hydrogen peroxide in all samples was found to be within the range 0.010–0.092 mM. The known correlation between the electrical conductivity and the color of honey was confirmed in this study. Univariate and multivariate statistics applied to the results indicate that the results can be used to discriminate honey sample groups of different botanical origins.